Triglyceride and Blood Glucose Levels in Diabetic Smokers and Non-Smokers: Tingkat Trigliserida dan Gula Darah pada Penderita Diabetes yang Merokok dan yang Tidak Merokok - Riantika, Mayang; Aliviameita, Andika (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Diabetes Mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and dyslipidemia, which often worsens with unhealthy lifestyle habits. Specific background: Smoking introduces toxic substances such as nicotine that can alter lipid metabolism, insulin sensitivity, and glucose regulation, thereby potentially aggravating complications in diabetic patients. Knowledge gap: While dyslipidemia and hyperglycemia in diabetes are well documented, evidence on the comparative differences between smokers and non-smokers with diabetes remains limited. Aim: This study investigated the differences in triglyceride and blood glucose levels among diabetic patients who smoke and those who do not. Results: An experimental design was conducted at Anna Medika Hospital Madura with 30 participants (15 smokers and 15 non-smokers with diabetes). The Mann Whitney test showed significant differences in triglyceride levels (p=0.000) and blood glucose levels (p=0.049) between the two groups, with smokers displaying higher values. Novelty: This study highlights nicotine’s role in exacerbating lipid and glucose dysregulation in diabetes within an Indonesian hospital setting. Implications: Findings emphasize the importance of targeted lifestyle interventions and smoking cessation programs in managing metabolic control among diabetic patients. Highlights: Smokers with diabetes had higher triglyceride and glucose levels. Nicotine worsens insulin resistance and lipid metabolism. Lifestyle modification is crucial for better diabetes management. Keywords: Diabetes Mellitus, Smoking, Triglycerides, Blood Glucose, Lifestyle